Implementation of a Multi-Modal Training Program for the Management of Comorbid Mental Disorders in Drug and Alcohol Settings: Pathways to Comorbidity Care (PCC). Issue 4 (2nd October 2021) - Louie, Eva; Morley, Kirsten C.; Giannopoulos, Vicki; Uribe, Gabriela; Wood, Katie; Marel, Christina; Mills, Katherine L.; Teesson, Maree; Edwards, Michael; Childs, Steven; Rogers, David; Dunlop, Adrian; et al.
Abstract: Objectives: We aimed to evaluate the impact of the Pathways to Comorbidity Care (PCC) training program for alcohol and other drugs (AOD) clinicians to improve the management of comorbidity. Methods: A controlled before-and-after study using PCC training was conducted across 6 matched sites in Australia including 35 clinicians. Controls received standard workplace training. PCC training included seminar presentations, workshops conducted by local "clinical champions, " individual clinical supervision, and access to an online information portal. We examined (a) identification (screening, assessment) and treatment (treatment, referral) of comorbidity in practice ( N = 10 clinical files per clinician), (b) self-efficacy, knowledge, and attitudes of clinicians. Results: Significant improvements were observed in the PCC group but not the control sites with regards to the rate of clinical files showing identification of comorbidity (+50% v −12% change from baseline, respectively; [ X 2 (1, N = 340) = 35.29, p = .01] with only a trend for improvements in the rate of files demonstrating treatment of comorbidity [ X 2 (1, N = 340) = 10.45, p = .06]. There were significant improvements in the PCC relative to the control group for clinician self-efficacy, F (1, 33) = 6.40, p = .02 and knowledge and attitudes of comorbidity monitoring, F (1, 33) = 8.745, p = .01. Conclusions: The PCC training package may help improve identification of comorbidity, self-efficacy, and attitudes toward screening and monitoring of comorbidity in drug and alcohol settings.